Shell and unified nuclear model calculations : shell model calculations with a surface delta effective interaction on light nuclei with 10 < A <15 and unified model calculations in weak and intermediate coupling on non-deformed odd-A nuclei, 45 Sc, 75 As and 93 Nb - Saayman, Rikus (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D..) -- University of Stellenbosch, 1972.